The relationship between intensity of gadget use and the level anxiety of parents with children 3-6 years old - Mihrawaty S. Antu; Nur Ayun R. Yusuf; Gusti Pandi Liputo; Fatia Ali (PT.Mantaya Idea Batara, 2024)
Technological progress is growing rapidly, especially the use of digital technology in the form of gadgets has been crazy about all walks of life, including children. The use of gadgets in children is currently very concerning, where the intensity of children's gadget use has exceeded normal limits both in frequency and frequency to spectacle. So that it causes feelings of anxiety in parents. The purpose of this study is to determine the relationship between the intensity of using gadgets and the anxiety level of parents who have children aged 3-6 years in Jaya Bakti village. This research is a quantitative research with a cross sectional approach. The sampling technique used purposive sampling with a total sample of 50 respondents. Data analysis used the Pearson Correlation test. The results of the study obtained a p value = 0.004, which means that there is a relationship between the intensity of using gadgets and the anxiety level of parents who have children aged 3-6 years in Jaya Bakti Village. It is hoped that parents can control, supervise, accompany and provide time limits for the intensity of using gadgets for children, so that they can reduce parents' anxiety levels.